2005
DOI: 10.1016/j.jecp.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Can one written word mean many things? Prereaders’ assumptions about the stability of written words’ meanings

Abstract: Pre-readers' assumptions about the stability of written words' meanings Abstract Results of 3 Experiments confirm previous findings that in a moving word task prereaders aged 3-5 years judge as if the meaning of a written word changes when it moves from a matching to a non-matching toy, for example when the word 'dog' moves from a dog to a boat. We explore under what circumstances children make such errors, and identify new conditions under which children were more likely correctly to treat written words' mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Children who are not confident about how print derives its meaning or believe that the picture has some role in attributing meaning to the print will change their answer to this question. The effectiveness of the moving word task to assess these concepts was replicated by Robinson and colleagues by using both standard procedures (Collins and Robinson, 2005) and other variations (Apperly and Robinson, 2003;Collins and Robinson, 2005). Moreover, in several studies, we have shown that bilingual children answer the incongruent question correctly at an earlier age than monolinguals (Bialystok, 1997(Bialystok, , 1999Bialystok, Shenfield and Codd, 2000;Bialystok and Senman, 2004).…”
supporting
confidence: 60%
“…Children who are not confident about how print derives its meaning or believe that the picture has some role in attributing meaning to the print will change their answer to this question. The effectiveness of the moving word task to assess these concepts was replicated by Robinson and colleagues by using both standard procedures (Collins and Robinson, 2005) and other variations (Apperly and Robinson, 2003;Collins and Robinson, 2005). Moreover, in several studies, we have shown that bilingual children answer the incongruent question correctly at an earlier age than monolinguals (Bialystok, 1997(Bialystok, , 1999Bialystok, Shenfield and Codd, 2000;Bialystok and Senman, 2004).…”
supporting
confidence: 60%